Pengaruh Permainan Outbound terhadap Penurunan Tingkat Stres Siswa Usia 13-15 Tahun - Nararia Kirana Bhakti; Ratna Candra Dewi (Pusat Riset dan Inovasi Nasional, 2023)
Academic stres is a condition of a student who feels pressured from outside himself that arises as a result of the demands of being superior to others. This study aimed to assess the stress levels of children between the ages of 13 and 15 before and after departure. A type of quasi-experimental research strategy was used in this study's quantitative research. Some of the games included clogs, ball relay, blind walk, and people-to-people. In this study, a one group, pretest-posttest design was used. The technique of choice for this study's sample, 166 junior high school children between the ages of 13 and 15, was purposeful sampling. utilising surveys using a Likert scale to collect data. Data analysis techniques using non-parametric statistics with a working method that uses SPSS 26 for windows as a calculation tool, namely descriptive analysis, prerequisite tests, and Wilcoxon tests with a significant α = 0.05. The results showed that there was an influence of outbound games on reducing student stres levels and obtained p = 0.001 (p < 0.05) with the average results of pre-test student stres levels (50.00) and post-test student stres levels (47.66). The conclusion of this study is that by giving treatment, namely fun games on outbound, it can reduce the stres level of students aged 13-15 years